## Equation of a Circle: Mastery Test 2 The equation x² + y2 – 2x + 2y – 1 = 0 is the general form of the equation of a circl

Question

Equation of a Circle: Mastery Test
2
The equation x² + y2 – 2x + 2y – 1 = 0 is the general form of
the equation of a circle. What is the standard form of the
equation?
(x – 1)2 – (y – 1)2 = 1
(x – 1)2 + (y + 1)2 = 3
© (x + 1)2 + (y – 1)2 = 4
(x – 1)² + (y + 1)2 = 1

in progress 0
2 months 2021-09-23T22:58:11+00:00 1 Answer 0 views 0

(x-1)^2+(y+1)^2=3

Step-by-step explanation:

x² + y2 – 2x + 2y – 1 = 0

add the 1 to get it to the other side of the equation

x² + y2 – 2x + 2y  = +1

group the x’s and y’s

(x² -2x) + (y2+2y) = +1

then you’ll complete the  square on the -2x and + 2y. that just means divide by two and then raise it to the 2nd power.

so (-2/2)^2 and (+2/2)^2

(x²-2x+1)+(y2+2y+1) = 1+1+1

you add the one’s to the other side because whatever is done to one side must be done to the other

you’ll then need to factor again.

(x-1)^2+(y+1)^2=3

to factor it take one of your squared x’s, the sign of the middle term within the parentheses , then the square root of the last term within the parentheses. remeber to put your ^2 (raised to the 2nd power) outside of the parentheses  when you finish.